Variation in Fitness among Geographically Isolated Colorado Potato Beetle (Coleoptera: Chrysomelidae) Populations. (1st January 2014) - Chen, Jie; Alyokhin, Andrei; Mota-Sanchez, David; Baker, Mitchell; Whalon, Mark
Abstract: Colorado potato beetle, Leptinotarsa decemlineata (Say), is a major pest of potatoes in North America, Europe, and parts of Asia. It adapts quickly to adverse environments, thereby limiting the longevity of control strategies. Better understanding of variability among geographically isolated populations of this insect might create an opportunity to customize control techniques for local conditions. We investigated insecticide resistance, heat tolerance, and growth potential in six beetle populations collected from different locations in the United States. Significant differences were detected in insecticide resistance, egg mass size, and egg hatchability among the tested populations. Large egg mass size appeared to be offset by lower egg hatchability. We also observed a female-biased sex ratio at least in one of the strains. Population growth rates were different among the strains, but this parameter was not correlated to insecticide resistance. This suggests that using allopatric populations in comparative studies of insecticide resistance might result in confusing effects of geographic isolation with the effects of selection toward resistance.